2021
DOI: 10.3390/ijms222010971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incubation Time on Ortho-Toluidine Blue Mediated Antimicrobial Photodynamic Therapy Directed against Selected Candida Strains—An In Vitro Study

Abstract: (1) Background and the aim: The appropriate incubation time in the antimicrobial photodynamic therapy protocol seems to have a huge impact on the efficacy of this process. This is particularly important in relation to Candida strains, due to the size of these cells and the presence of the cell wall. The aims of this study were to determine the optimal incubation time needed for the absorption of toluidine blue by cells of C. albicans, C. glabrata, C. krusei and C. parapsilosis using direct observation by optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, this was not the case with the C. albicans strain, where increased incubation time was ineffective for BGBE uptake (P>0.05). This result contradicts the findings of Wiench et al (2021) [12].…”
Section: Discussioncontrasting
confidence: 85%
“…However, this was not the case with the C. albicans strain, where increased incubation time was ineffective for BGBE uptake (P>0.05). This result contradicts the findings of Wiench et al (2021) [12].…”
Section: Discussioncontrasting
confidence: 85%
“…long incubation time ensures adequate absorption and quantity of PSs in target cells. With the extension of incubation time (before saturation), PDT becomes more antibacterial[53]. Our previous in vivo studies verified that the production of PpIX increased significantly after incubation in ALA for 3 h and reached the highest level after 6 h[26,27].…”
mentioning
confidence: 70%
“…To the best of our knowledge, there is no reported effect when using just red light on C. albicans species. Wiench et al reported that due to the size of Candida cells and the presence of the cell wall, photosensitizer incubation time has an impact on PDT efficacy and suggested 7-10 min as the most efficient period [ 38 ]. Despite those findings, the application and incubation period of photosensitizing solution in the oral cavity with the salivary flow and long clinician chairside time makes this approach impractical in clinical practice.…”
Section: Discussionmentioning
confidence: 99%